Analyzing the Level of Rural Settlement Services based on Distributed Justice(case study: Tankeman district) - gholam dolati; hasan afrakhte; farhad azizpor; taher parizadi (تحقیقات کاربردی علوم جغرافیایی)
Rural services and the power and location of rural services are one of the important issues in planning. In examining patterns and systems of rural services, the status and importance of each village in terms of utilizing a variety of rural services and its ability to receive or transfer Services are considered as an essential element and element. The spatial analysis of services can be described and explained in the context of distributive justice. The rural areas of the Tankeman district of the Alborz province have faced rural immigration in recent years, while faced with challenges in terms of enjoying some rural services. In order to plan and optimize the rural service system in this section, it is necessary first of all to evaluate the situation of each village in terms of utilizing rural services. Based on this, by providing a questionnaire from 16 selected villages in this section, the status of each village was evaluated for different types of rural services based on the number of existing services and the decision matrix was formed and then through Antherapy method, the weight of each specified service and then prioritized by using COPRAS  model. The results show that the main village has basic services. But they are facing challenges with modern and new services. Accordingly, the villages of Bakhtiar, Nukand and Mohammad Abad Khalisheh, Kareem Abad, Qasem Abad and Dengizak have the most benefit from rural services, and this situation follows a cluster pattern.